Total synthesis of justicidin B, justicidin E, and taiwanin C: A general and flexible approach toward the synthesis of natural arylnaphthalene lactone lignans - Wei, Kai; Sun, Yucui; Xu, Yiren; Hu, Wen; Ma, Ying; Lu, Yi; Chen, Wen; Zhang, Hongbin (Frontiers in Chemistry, 2022)
Lignans are widely present in traditional medicinal plants. Many natural arylnaphthalene lactone lignans (NALLs) isolated from the genera Justicia, Haplophyllum, and Phyllanthus possess interesting biological activities. Herein, we report a general strategy for the total synthesis of this kind of lignans. Features of this new approach are an aryl–alkyl Suzuki cross-coupling to introduce the dioxinone unit, a cation-induced cyclization to construct the aryl dihydronaphthalene, and base-mediated oxidative aromatization to furnish the arylnaphthalene core. By incorporating these key transformations, the total syntheses of justicidins B and E and taiwanin C covered type I and type II NALLs were accomplished.